Revisiting the psychology of waste: Replication and extensions Registered Report of Arkes (1996) - Zijin Zhu; Gilad Feldman (Royal Society Open Science)
Arkes (Arkes 1996 J. Behav. Decis. Mak. 9, 213–224. (doi:10.1002/(SICI)1099-0771(199609)9:3<213::AID-BDM230>3.0.CO;2-1) demonstrated a phenomenon of wastefulness avoidance, showing that people’s decisions are impacted by wastefulness, making decisions that avoid appearing wasteful. In a Registered Report with a Prolific sample (N = 659), we conducted a replication and extensions of studies 1, 2 and 3 from Arkes, 1996. We found empirical support for the impact of waste on evaluations of decisions in the movie package scenario in study 1 (original: h = 0.43 [0.03, 0.83]; replication: h = 0.26 [0.10, 0.42]) and on hypothetical decisions in the tent project scenario in study 3 (original: w = 0.23 [0.00, 0.52]; replication: w = 0.09 [0.00, 0.17]), but with no support in the tax program scenario in study 2 (original: w = 0.27 [0.00, 0.55]; replication: w = 0.03 [0.00, 0.12]). Our extension employing a continuous willingness measure, to supplement the scenarios’ dichotomous choice, showed similar results. We added a manipulation check extension, which showed that the manipulation worked as expected in scenarios 1 and 3, but not in scenario 2. In our extension examining reasons, in the successfully replicated scenarios, we found that in scenario 1, utility maximization was not rated as the most important, and in scenario 3, minimizing waste was rated as the most important reason. Overall, we concluded a mixed replication, with a successful replication of two of the three tested studies. Materials, data and code are available at https://osf.io/gf8rc/. This Registered Report has been officially endorsed by Peer Community in Registered Reports: https://doi.org/10.24072/pci.rr.100801.